2013
DOI: 10.1158/1055-9965.epi-13-0229
|View full text |Cite
|
Sign up to set email alerts
|

Association between 8-oxo-7,8-dihydro-2′-deoxyguanosine Excretion and Risk of Postmenopausal Breast Cancer: Nested Case–Control Study

Abstract: Background: Oxidative stress may be important in carcinogenesis and a possible risk factor for breast cancer. The urinary excretion of oxidatively generated biomolecules, such as 8-oxo-7,8-dihydro-2 0 -deoxyguanosine (8-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 48 publications
2
46
1
2
Order By: Relevance
“…Samples from cases were collected at cohort entry within 5 years of diagnosis. Overall, a positive association between 8-oxodG and risk of breast cancer was observed, 30 and when stratified by ER status, the positive association was limited to women with ER+ breast cancer. In 2015, a large nested casecontrol study focusing on premenopausal breast cancer in the Nurses' Health Study I and II studies reported some evidence for an inverse association for FlOPs and premenopausal breast cancer (e.g., FlOP_360 highest quartile levels [compared with lowest quartile levels] were associated with a 32% decreased risk of premenopausal breast cancer in adjusted models).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Samples from cases were collected at cohort entry within 5 years of diagnosis. Overall, a positive association between 8-oxodG and risk of breast cancer was observed, 30 and when stratified by ER status, the positive association was limited to women with ER+ breast cancer. In 2015, a large nested casecontrol study focusing on premenopausal breast cancer in the Nurses' Health Study I and II studies reported some evidence for an inverse association for FlOPs and premenopausal breast cancer (e.g., FlOP_360 highest quartile levels [compared with lowest quartile levels] were associated with a 32% decreased risk of premenopausal breast cancer in adjusted models).…”
Section: Resultsmentioning
confidence: 89%
“…28 One study reported that the positive association of 8-oxodG was only present in women with low dietary iron intake; p-value for interaction = 0.02. 30 Oxidative stress biomarkers and breast cancer prognosis Study design and study population details are displayed in Table 3 and results are summarized in Table 4. We identified a total of eight studies that investigated biomarkers of oxidative stress in association with breast cancer prognosis with various oxidative stress biomarkers in blood, urine, and tissue utilized.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study of human subjects exposed to airport noise overnight in their home showed endothelial dysfunction, which was attenuated by administration of the antioxidant vitamin C [10]. Converging lines of evidence indicate that exposure to traffic noise is associated with the risk of breast cancer [11], of which risk factors for the latter could also include oxidative stress and urinary 8-oxodG excretion [12]. Accordingly, traffic-related air pollution and noise not only share sources, but also adverse health effects and these exposures might converge in some of the mechanistic pathways and act synergistically.…”
Section: Introductionmentioning
confidence: 99%